Drug Repurposing of the Alcohol Abuse Medication Disulfiram as an Anti-Parasitic Agent - Shirley, Debbie-Ann; Sharma, Ishrya; Warren, Cirle A.; Moonah, Shannon (Frontiers in Cellular and Infection Microbiology, 2021)
Parasitic infections contribute significantly to worldwide morbidity and mortality. Antibiotic treatment is essential for managing patients infected with these parasites since control is otherwise challenging and there are no vaccines available for prevention. However, new antimicrobial therapies are urgently needed as significant problems exist with current treatments such as drug resistance, limited options, poor efficacy, as well as toxicity. This situation is made worse by the challenges of drug discovery and development which is costly especially for non-profitable infectious diseases, time-consuming, and risky with a high failure rate. Drug repurposing which involves finding new uses for existing drugs may help to more rapidly identify therapeutic candidates while drastically cutting costs of drug research and development. In this perspective article, we discuss the importance of drug repurposing, review disulfiram pharmacology, and highlight emerging data that supports repurposing disulfiram as an antiparasitic, exemplified by the major diarrhea-causing parasite Entamoeba histolytica.